Gelora (Gerakan Literasi Kolaboratif) Perpustakaan Harati dan SD Negeri 1 Kereng Bangkirai sebagai Bentuk Implementasi Perda Kota Palangka Raya Nomor 9 Tahun 2019 Tentang Penyelenggaraan Perpustakaan di Kelurahan Kereng Bangkirai - Rio Pratama; Kumalasari, Intan; Bhayu Rhama; Nurul Hikmah; Gradila Apriani; Iin Aprillina; Yonatan Ari Santoso; Melia Sintha; Murraya Putri Palupi; Pambajeng Luluh Dyah Pangestu (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
The low literacy rate and limited infrastructure continue to be ongoing issues in the city of Palangka Raya. As an effort to improve the literacy value of the community, especially in the narrower social sphere. Therefore, in this case, the establishment of libraries at the Village or Subdistrict Government level is very much needed. As a step to regulate the management and organization of libraries from the city level to the sub-district level, the Palangka Raya City Government has enacted Regional Regulation No. 9 of 2019 concerning Library Management. This Community Service Program focuses on improving community literacy, particularly for students of SD Negeri 1 Kereng Bangkirai, conducted in the village of Kereng Bangkirai. Thru this activity, it is expected that there will be an increase in community visits to the "Harati" Library in the village of Kereng Bangkirai and that it will enhance interest and awareness of literacy, especially among the students of SD Negeri 1 Kereng Bangkirai. Thus, this Community Service activity can run and have a maximum impact.